2013
DOI: 10.1136/bmj.f4930
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury: summary of NICE guidance

Abstract: This is one of a series of BMJ summaries of new guidelines based on the best available evidence; they highlight important recommendations for clinical practice, especially where uncertainty or controversy exists. Correspondence to: M Thomas mark.thomas@heartofengland.nhs.uk For personal use only: See rights and reprints

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 9 publications
4
47
0
Order By: Relevance
“…In our study, 40% of patients with CKD admitted to the emergency department had community‐acquired AKI. Although this rate is far higher than the incidence rate found in the largest study on community‐acquired AKI, this is likely explained by our selection criteria that focused our study on patients most susceptible to AKI who present with frequent comorbidities such as moderate to severe CKD, diabetes mellitus, arterial hypertension, and older age . Accordingly, the mean age of our cohort was 77 years, which is consistent with other epidemiologic studies on community‐acquired AKI .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, 40% of patients with CKD admitted to the emergency department had community‐acquired AKI. Although this rate is far higher than the incidence rate found in the largest study on community‐acquired AKI, this is likely explained by our selection criteria that focused our study on patients most susceptible to AKI who present with frequent comorbidities such as moderate to severe CKD, diabetes mellitus, arterial hypertension, and older age . Accordingly, the mean age of our cohort was 77 years, which is consistent with other epidemiologic studies on community‐acquired AKI .…”
Section: Discussionsupporting
confidence: 84%
“…In patients with CKD, RAS blockers are recommended mainly for both arterial hypertension and proteinuria to slow the rate of CKD progression . However, RAS blockers may induce acute kidney injury (AKI) in certain clinical situations such as dehydration or sepsis, which are frequently reported in elderly patients with CKD . In turn, AKI itself may hasten the progression of the underlying CKD by causing cell cycle arrest of tubular cells and the development of interstitial renal fibrosis .…”
Section: Dosing Of Most Prescribed Ace Inhibitors and Arbsmentioning
confidence: 99%
“…34 Moreover, clinical decision support systems that ensure proper drug dosing in patients with AKI may be of particular value, because older adults frequently have impaired drug clearance in addition to polypharmacy. 35 …”
Section: Discussionmentioning
confidence: 99%
“…NICE has suggested that chronic renal disease should be classified to include patients with kidney damage who are at risk of progressing to failure (Table 1). In 2013, the Kidney Disease: Improving Global Outcomes (KDIGO) guidance on the evaluation and management of chronic kidney disease adopted the subdivision of glomerular filtration rate (GFR) categories suggested by the NICE guideline, but also included three albumin:creatinine ratios (ACRs) for each GFR category in an updated classification 3 (Table 2).…”
mentioning
confidence: 99%